1999
DOI: 10.1080/14622299050011791
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity, gender and risk factors for smoking initiation: An overview

Abstract: Although the prevalence of cigarette smoking has increased dramatically among youth over the past several years, there are significant ethnic and gender differences in prevalence rates. This paper presents highlights of the research literature on ethnic and gender differences in risk factors for smoking. The effects of peer and family influences may vary by both ethnicity and gender. White youth, especially females, may be more susceptible to the negative influence of friends' smoking than are African-American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 22 publications
0
25
1
2
Order By: Relevance
“…This increased awareness may extend to smoking behaviors, making the perceived smoking environment a stronger predictor of girls' smoking than boys' [26 -29]. However, the few studies that have examined this hypothesis among multi-ethnic youth found that the increased vulnerability to the perceived environment was observed among white girls and not girls from other racial/ethnic groups [15,30].…”
mentioning
confidence: 96%
“…This increased awareness may extend to smoking behaviors, making the perceived smoking environment a stronger predictor of girls' smoking than boys' [26 -29]. However, the few studies that have examined this hypothesis among multi-ethnic youth found that the increased vulnerability to the perceived environment was observed among white girls and not girls from other racial/ethnic groups [15,30].…”
mentioning
confidence: 96%
“…Environmental factors are also modified by ethnicity; this is, e.g. the case for tobacco use, perception of health risk, or social unacceptability [132]. However, in non-genomic studies, ethnicity is usually not considered as a factor of interest; either mixed ethnicities are used or there is no information on it.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to race and ethnicity, the role of gender in smoking initiation in adolescence has produced inconclusive results 1,10,14,15 . A number of studies have identified being male as a risk factor for smoking initiation 10,14,15 while other studies have found that being female was associated with higher prevalence for this behavior 2,4 . The 2014 Surgeon General Report found no gender differences in adolescent cigarette smoking initiation 1 .…”
Section: Demographic Factors and Cigarette Smoking Initiationmentioning
confidence: 99%
“…This statistical inference method is used to determine whether or not an effect exists between a set of variables based on an alpha cut-off value (e.g. p < .05) [9][10][11][12][13][14][15][16][17][18][19][20][21][22] . However, alpha is highly influenced by large samples and likely to produce significant differences between variables, even if such differences are negligible 21,22 .…”
Section: Addressing the Inconsistenciesmentioning
confidence: 99%